2023
DOI: 10.3389/fnut.2023.1237869
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetylcysteine on aging cell and obesity complications in obese adults: a randomized, double-blind clinical trial

Mohammad Hassan Sohouli,
Ghazaleh Eslamian,
Nasser Malekpour Alamdari
et al.

Abstract: BackgroundWe decided to conduct this study with the aim of investigating the effects of N-Acetylcysteine (NAC) on obesity complications and senescence of visceral adipose tissue in obese adults.Methods and analysisThe present study was conducted as a randomized clinical trial (RCT) (Clinical trial registry number: IRCT20220727055563N1) on 40 obese adults candidates for bariatric surgery, who were randomly assigned to receive 600 mg of NAC (n = 20) or placebo as a control (n = 20) for 4 weeks. During bariatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Senescent T-cells gradually accumulate in organisms as they age and cause chronic inflammation in adjacent tissues through the secretion of SASP. This process leads to a deterioration in organ function and contributes to the development of several age-related chronic conditions, including cardiovascular disease, endocrine and metabolic disorders, cancer, Alzheimer's disease, and autoimmune diseases [ 9 12 ]. During the process of chronological aging, various types of cells undergo cellular senescence, leading to the development of a senescent phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Senescent T-cells gradually accumulate in organisms as they age and cause chronic inflammation in adjacent tissues through the secretion of SASP. This process leads to a deterioration in organ function and contributes to the development of several age-related chronic conditions, including cardiovascular disease, endocrine and metabolic disorders, cancer, Alzheimer's disease, and autoimmune diseases [ 9 12 ]. During the process of chronological aging, various types of cells undergo cellular senescence, leading to the development of a senescent phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Most types of cells in both the innate and adaptive immune systems undergo age-related alterations, particularly T-cells, which have a greater potential capacity for proliferatio [ 18 ]. Furthermore, chronic low-grade inflammation caused by senescence in adipose tissue and immune cells contributes to the development of obesity-related diseases [ 12 , 19 ], involves a complex interplay of immune system responses, including acquired immunity mediated by T and B cells, as well as innate immunity involving macrophages [ 20 , 21 ]. Previous studies have shown that obesity accelerated immunosenescence, independent of chronological aging [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%